The effect of feed barrier design on displacements during feeding of dairy cows in small herds. (2nd January 2018) - Bøe, K. E.; Hansen, G.; Ruud, L. E.
ABSTRACT: The aim of this study was to investigate the effect of feed barrier design on displacements in dairy cows fed only roughage diets in the bunk in small commercial dairy herds. Six Norwegian dairy herds with open barriers (OB) and six herds with individual headspace barriers (IHB) were randomly selected. Number of displacements and withdrawals without physical contact was somewhat higher, but not significantly higher, in the IHB herds than in the OB herds but the variation between herds within the type of barrier were very large. The number of pushes and buttings directed towards the front part of the body of cows was significantly higher in the OB herds than in the IHB herds whereas pushes and butts directed towards the side of cows were significantly higher in the IHB herds than in the OB herds.